Pengaruh Komitmen Kerja Terhadap Kepuasan Kerja Pegawai Kantor Lembaga Pemasyarakatan Kelas 1 Bandar Lampung - Heylin Idelia Jayasinga; Nety Kumalasari (Universitas Mitra Indonesia, 2020)
AbstractThis study aims to determine the effect of work commitment on job satisfaction at the Class 1 Correctional Institution office in Bandar Lampung. Research carried out quantitative research. This study used 35 research respondents. There are two variables in this study, namely: 1 (one) independent variable (X) and 1 (one) dependent variable where work commitment (X) is the independent variable and job satisfaction (Y) as the dependent variable. The amount of the coefficient of determination between work commitment to job satisfaction is 15.3%. These results indicate that there is an effect of work commitment on job satisfaction at the Class 1 Correctional Institution office in Bandar Lampung, 15.3%. The suggestions put forward by the researcher are as follows: Work commitment variable, which needs attention to increase this indicator is that employees have an educational background relevant to their work position because the indicator value is the lowest. The leadership can increase this indicator by providing jobs and tasks according to the background and basics of employees. The job satisfaction variable that needs attention is an indicator about the employee completing the work not exceeding the promised time limit because this indicator gets a low score. This indicator enhancement can be done by the leadership by placing the position of employees according to their prudence and assigning jobs according to the job description they have, because thus the work can be done more effectively and efficiently. Keywords: work commitment and job satisfaction